Advances in Magnetic‐Field Assisted Photoelectrochemical Systems for Highly Efficient Conversion of Renewable Energy. Issue 16 (26th July 2021) - Yan, Xiaohui; Li, Gang; Yu, Zhichao; Liu, Guohua; Yang, Changping; Hu, Jifan; Wang, Kaiying
Abstract: Industry‐scaled water splitting is one of the achievements in the application chains of sustainable hydrogen energy. Numerous strategies have been used to increase the efficiency in photoelectricity (PE)/photoelectrochemistry (PEC) systems, involving enhancing charge transfers and active surface area. However, the efficiency of PE/PEC water splitting is still confined by the high overpotential of the PE/PEC reactions, unexpected loss of electron migration, and low stability of photocatalytic electrodes. Recently, various magnetically‐enhanced techniques have emerged as promising strategies to improve the conversion efficiency of renewable energy. Herein, this work summarizes recent progress on magnetically‐enhanced methods for promoting PEC water splitting performance. Then magnetism in the PE applications is discussed, such as magnetic sensors, modulators, and isolators. As a summary, future research directions and challenges of magnetic PEC with different magnetic effects and conditions are discussed for enhancing the PEC reactions. Abstract : This review paper summarizes recent progress on magnetic‐field assisted technique for promoting photoelectrochemistry water splitting performance. It also discusses intrinsic/extrinsic magnetic materials for the photoelectricity applications.